2D Material‐Enabled Optical Rectennas with Ultrastrong Light‐Electron Coupling. Issue 37 (22nd July 2022) - Nguyen, Hai‐Thai; Yen, Zhi‐Long; Su, Yen‐Hsun; Hsieh, Ya‐Ping; Hofmann, Mario
Abstract: Optical rectennas extend the electromagnetic wave rectification process into the visible regime and provide a route toward high‐performance photodetection and energy harvesting. Here, the promise of 2D materials toward on‐chip optical rectennas is demonstrated. A self‐aligned patterning process yields lateral MIM structures where a nanometer‐sized air gap separates a 2D material contact from a metal electrode. This device can be scalably produced in large arrays using established microfabrication techniques. Different from previous approaches, the performance of the 2D rectenna can be adjusted through electrostatic gating. Optimization of the band alignment leads to strong rectification at wavelengths around 500 nm and clear polarization control. Comparison of wavelength‐dependent rectenna performance with a photon‐assisted tunneling model reveals a tenfold increase in photon‐electron coupling over nanotube‐based rectennas. The results highlight the potential of 2D material‐based rectennas for future quantum computing applications. Abstract : 2D materials‐based gapped‐edge contacts help realize efficient rectification of the optical field into direct current due to improved photon capture and conversion.